Clinical effects of high arteriovenous fistula with different anastomotic diameters - LIN Ye; CHEN Wen; HU Xue-qin; ZHUANG Yi-jun (Linchuang shenzangbing zazhi)
Objective To observe the effectiveness and complications of arteriovenous fistula with different anastomotic diameters in hemodialysis. Methods Thirty-six inpatients with endstage of renal diseases in our hospital from January 2014 to November 2016 were unable to perform operations for routine arteriovenous fistula in hemodialysis. There were 21 males and 15 females,they were selected to operate for the high arteriovenous fistula surgery,and postoperative ultrasound displayed there were 20 cases of anastomotic diameter of 4-6 mm( group A) and 16 cases of diameter greater than 6 mm( group B). The fistula maturation time,time of initial application,blood flow of fistula,and the incidence of complications such as fistula occlusion,thrombosis,heart failure,pseudoaneurysm,steal syndrome and swelling of hands. Results The high arteriovenous fistulae were successfully established in all 36 patients in the first operation. The immediate patency rate of arteriovenous fistula was 100%,and no postoperative infection occurred. There were no significant differences between two groups in the fistula maturation time,time of initial application,incidence of fistula occlusion,thrombosis,steal syndrome,and swollen hand syndrome( P > 0. 05). The incidence of heart failure and pseudoaneurysm in group A was significantly lower than in group B( P <0. 05). Conclusions High arteriovenous fistula surgery with sufficient blood flow and high patency rate,was the best choice for the patients having contraindication of establishing vascular access for forearm arteriovenous fistula. By strictly controlling the anastomotic size of high arteriovenous fistula,we can ensure the blood flow in hemodialysis,and reduce the incidence of heart failure and other related complications.